2010
DOI: 10.1002/tax.591009
|View full text |Cite
|
Sign up to set email alerts
|

The Afro‐Madagascan genusWarneckea(Melastomataceae): Molecular systematics and revised infrageneric classification

Abstract: Warneckea consists of shrubs and small trees endemic to tropical forests in Africa, Madagascar, and Mauritius. Phylogenetic analyses of sequence data from the transcribed spacers of nuclear ribosomal DNA (ETS, ITS) indicate that W. sect. Carnosa Jacq.‐Fél. (1 sp., East Africa and Madagascar) is a divergent element that is best treated at subgeneric level. The analyses recovered three major lineages in W. subg. Warneckea, together forming a basal trichotomy. The three lineages represent W. sect. Strychnoidea (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…Warneckea cordiformis is placed in W. subgenus Carnosae on account of its combination of leaf blades with conspicuous network of purplish veinlets on the lower surface; sessile inflorescences agglomerated at the recently defoliated nodes; floral pedicels subtended by persistent, imbricate‐decussate bracts; patelliform calyx limb with lobes obsolete; and anther connectives bearing a minute, dorsal oil‐gland (Stone and Andreasen 2010). The new species would key to W. sansibarica in ‘Flora Zambesiaca’ and ‘Flora de Moçambique’ (Fernandes and Fernandes 1978, 1980), but is readily distinguished from W. sansibarica and other members of W. subgenus Carnosae by its relatively small, ovate to cordiform leaves and white flowers borne on short pedicels.…”
Section: Warneckea Cordiformis R D Stone Sp Nov (Fig 1)mentioning
confidence: 99%
See 4 more Smart Citations
“…Warneckea cordiformis is placed in W. subgenus Carnosae on account of its combination of leaf blades with conspicuous network of purplish veinlets on the lower surface; sessile inflorescences agglomerated at the recently defoliated nodes; floral pedicels subtended by persistent, imbricate‐decussate bracts; patelliform calyx limb with lobes obsolete; and anther connectives bearing a minute, dorsal oil‐gland (Stone and Andreasen 2010). The new species would key to W. sansibarica in ‘Flora Zambesiaca’ and ‘Flora de Moçambique’ (Fernandes and Fernandes 1978, 1980), but is readily distinguished from W. sansibarica and other members of W. subgenus Carnosae by its relatively small, ovate to cordiform leaves and white flowers borne on short pedicels.…”
Section: Warneckea Cordiformis R D Stone Sp Nov (Fig 1)mentioning
confidence: 99%
“…The genus Warneckea Gilg comprises about 50 species of shrubs or small trees restricted to humid forests in Africa, Madagascar and Mauritius. Further morphological and molecular studies have shown that it is distinct from Memecylon L. (Jacques‐Félix 1978b, Stone 2006, Stone and Andreasen 2010). In the treatment of Memecylon s.l.…”
mentioning
confidence: 99%
See 3 more Smart Citations